South Africa : Technical Assistance Report-Petroleum Sector Fiscal Regime Reform-Additional Analysis for the Davis Tax Committee. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Technical Assistance report lists key issues discussed between the IMF's Fiscal Affairs Department (FAD) and the Davis Tax Committee regarding recommendations for tax reforms in the oil and gas sector in South Africa. It is suggested that the royalty should have a single flat rate, rather than the current variable rate formula. The 5 percent flat rate proposed in the FAD report is modest by international standards. For corporate tax purposes, the current immediate expensing of capital expenditure and the 100 percent and 50 percent uplifts for exploration and development expenditure are overly generous and will lead to both a revenue loss and a long delay before revenue is collected.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet